MENINGKATKAN KEMAMPUAN MENGIDENTIFIKASI KARAKTERISTIK DEWA TRI MURTI DENGAN MEDIA HALILINTAR MELALUI PENDEKATAN MULTISENSORI BAGI SISWA TUNARUNGU KELAS II SDLB DI SLB N 1 BADUNG: MENINGKATKAN KEMAMPUAN MENGIDENTIFIKASI KARAKTERISTIK DEWA TRI MURTI DENGAN MEDIA HALILINTAR MELALUI PENDEKATAN MULTISENSORI BAGI SISWA TUNARUNGU KELAS II SDLB DI SLB N 1 BADUNG - Ayu Putu Dewi Ary Sukanti (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Deaf students are students who have obstacles in hearing and speaking, with this situation, of course, it will also have an impact on the process of obtaining education. Their inability to hear causes obstacles in obtaining information. Therefore, Deaf students optimize their sense of sight, their ability to see is very good, Deaf students are often called Visual people. The use of media in the teaching and learning process can make it easier for students to master the lessons delivered by the teacher, especially visual education media. This can be seen from the ability to identify the characteristics of Dewa Tri Murti for Deaf students in class II SDLB B at SLB N 1 Badung which increased after using the Lightning media with a multisensory approach. It can be seen from the results of Class Action research through 2 cycles using the Kemmis model of classroom action research design. & McTaggart with the results of an increase in students' ability to identify the characteristics of Dewa Tri Murti with Halilintar media through a multisensory approach, which increased from cycle I to cycle II. The classical learning completeness of the knowledge test in the first cycle is 60% and in the second cycle it is 80%, meaning that it has increased by 20%. The classical learning completeness of the first cycle of performance tests is 60% and in the second cycle of 100%, it means that there is an increase of 40%.